2021
DOI: 10.1049/mia2.12081
|View full text |Cite
|
Sign up to set email alerts
|

Flexible circularly polarized antenna with axial ratio bandwidth enhancement for off‐body communications

Abstract: A flexible circularly polarized (CP) wearable antenna is proposed for a wireless body area network at the 5.8-GHz industrial, scientific, and medical band. The proposed antenna is made of flexible polyimide and foam material. The CP radiation is enabled by loading two pairs of shorting pins on a rectangular patch antenna. The 3-dB axial ratio (AR) bandwidth is doubled by adding two inverted L-shaped parasitic stubs on both sides of the antenna. For validation, the antenna with the dimensions of 0.68λ 0 � 0.68λ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In this paper, a wearable bra is proposed to monitor and scan for breast cancer. This Smart Bra is presented as a component of a WBAN system such that women will not need to regularly visit a hospital [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, a wearable bra is proposed to monitor and scan for breast cancer. This Smart Bra is presented as a component of a WBAN system such that women will not need to regularly visit a hospital [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is a good choice for encountering multipath fading and establishing reliable channels when compared with linearly polarized (LP) antennas, especially in crowded interior environments [ 1 , 2 , 3 , 4 , 5 ]. However, only a few works focus on the CP MS wearable antennas [ 1 , 2 , 3 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the most reported CP antennas applied for WBAN applications are based on rigid substrates, which cannot exhibit conformal characteristics. In this area, few research works on CP wearable antennas have been reported [29]- [32]. The multilayer flexible CP antenna is introduced in [29].…”
Section: Introductionmentioning
confidence: 99%
“…In this area, few research works on CP wearable antennas have been reported [29]- [32]. The multilayer flexible CP antenna is introduced in [29]. In [30], a costly CP antenna has been suggested by using flexible polydimethylsiloxane (PDMS) as a substrate.…”
Section: Introductionmentioning
confidence: 99%
“…21 However, non-flexible substrates could not comfort in the proximity of the body. Therefore, flexible substrates, such as textile, 22 were utilized to design wearable CP antennas. Besides, some other CP wearable antennas with narrow axial ratio (AR) bandwidth are reported in Reference 23.…”
Section: Introductionmentioning
confidence: 99%